Study case of impacts in power quality and analysis of time varying harmonics produced by photovoltaic inverters under transient conditions. - GOMES, Ricardo Oliveira (2019)
As renewable energy use increases mainly by photovoltaic generation, a large number of inverters are connected to the grid creating harmonic distortion. Each inverter topology and control methodology has advantages and disadvantages. A comparative study was carried out between the three main internal inverters topologies, analyzing their contente and harmonic distortion (THD). A second study was carried out on two models of Fronius inverters, located at na university building with photovoltaic plant of 27kWp. Measurements were taken at the building substation and directly at inverters outputs analyzing standard operation, startup, shutdown and energy variation due to solar irradiation. To perform these analyzes, time-frequency analysis techniques such as STFT, Wavelet and Wavelet Packet were used. The techniques are effective to analyze and identify the harmonic system components, as well as increase in magnitude over time. In addition, the techniques were also effective on identifying the behavior of other loads and their harmonics propagation in the grid.